Estimates of Ad Valorem Equivalents of Barriers Against Foreign Suppliers of Services in Eleven Services Sectors and 103 Countries. (12th October 2015) - Jafari, Yaghoob; Tarr, David G.
Abstract: A new database on the barriers faced by foreign suppliers of services has been produced by the World Bank. Data for 103 countries are available on eleven of the most important services sectors in international trade. To date, however, these data have not been converted into ad valorem equivalents. Based on these data, and building on the methodology and publications supported by the Australian Productivity Commission, we produce estimates of the ad valorem equivalents of the barriers for all these sectors and countries. Compared with estimates available in the literature that are based on assessments of country and sector‐specific barriers to services providers, our estimates expand the set of sectors and more than triple the set of countries for which estimates of the ad valorem equivalents of the services barriers are available.